Exploitation and Conservation - Azka Nisa Shafira; Pratiwi Retnaningdyah (Pioneer: Journal of Language and Literature, 2022)
Employing ecology as the pivotal basis of its narrative, Dune by Frank Herbert is regarded as the pioneer of ecological science-fiction novels. This qualitative study intends to examine the exploitation and conservation of nature and how human background influences such behaviours in Frank Herbert’s Dune. The researcher employs an ecocritical approach to literature to discuss the compiled textual data. Through the thematic analysis technique, this article reveals how Dune highlights the issues of the authority party and the indigenous society of Arrakis triggered by the abundance of the spice melange and the absence of water and vegetation, where these two sides of the population have contradictory intentions towards natural resources—exploiting and conserving. Moreover, the study unveils that the extortion attempts of the Galactic Imperium, the Harkonnens, CHOAM, and the Spacing Guild are driven by political and economic motives, and the conservation effort of the Fremen and the Atreides is the outcome of their ecological awareness.